1996
DOI: 10.1002/jlb.59.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Development, differentiation, and phenotypic heterogeneity of murine tissue macrophages

Abstract: In murine ontogeny, macrophage precursor cells develop in the yolk sac and fetal liver. Primitive macrophages also appear in the yolk sac, migrate to various tissues, and differentiate into several fetal macrophage populations. Because the development of the monocytic cell lineage is incomplete in the early stage of fetal hematopoiesis, primitive/fetal macrophages are considered to originate from granulocyte-macrophage colony forming cells or earlier macrophage precursors, bypassing the early monocytic cell se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(112 citation statements)
references
References 39 publications
5
104
1
2
Order By: Relevance
“…Indeed, MP show unique proteomic profiles even when cultured under identical conditions. These results serve to extend prior MP phenotypic heterogeneity studies, including M-CSF dependency (Cecchini et al, 1994;Naito et al, 1996;de Villier et al, 1998).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Indeed, MP show unique proteomic profiles even when cultured under identical conditions. These results serve to extend prior MP phenotypic heterogeneity studies, including M-CSF dependency (Cecchini et al, 1994;Naito et al, 1996;de Villier et al, 1998).…”
Section: Discussionsupporting
confidence: 73%
“…Whether this translates into functional (Gordon et al, 1988) and antigenic differences (Taylor et al, 2003;Guillemin and Brew, 2004) is not completely understood. MP heterogeneity may be simply a consequence of cell exposure to the tissue microenvironment including local growth factors (Naito et al, 1996). The latter would include, but not be limited to, macrophage and granulocyte-macrophage colony-stimulating factors (M-CSF and GM-CSF), that affect MP differentiation, proliferation and activation (Kaplan et al, 1992;Cecchini et al, 1994;de Villiers et al, 1994de Villiers et al, , 1998Hamilton, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a recent resurgence of the debate over the exact topography of HSC emergence in the mammalian embryo (Samokhvalov et al, 2007), the prevalent view on blood formation is that it follows a two-wave model (reviewed in Godin and Cumano, 2002). The first wave of haematopoiesis-mouse embryonic days (E) 7-8.5-produces primitive erythrocytes (both nucleated and enucleated; Kingsley et al, 2004), megakaryocytes (Tober et al, 2007) and macrophages (Naito et al, 1996), that emerge as uni-and bilineage-committed progenitors (Tober et al, 2007); it does not produce HSC as defined by the capacity to reconstitute haematopoiesis in an adult organism (Cumano et al, 2001). In mammals, this inaugural blood production is extra-embryonic and locates to the blood islands in the YS.…”
Section: Developmental Contexts In Haematopoiesismentioning
confidence: 99%
“…Accordingly, when cultured in vitro in the presence of the cytokines M-CSF or GM-CSF, monocytes can be driven to differentiate into M⌜ and DC, respectively (3,4). Furthermore, in vivo studies also provide evidence that blood monocytes can act as precursors of M⌜ (1,5,6). More recent reports have shown that monocytes can under inflammatory conditions differentiate in vivo into conventional CD11c high DC (cDC) (7,8) and Langerhans cells (9).…”
mentioning
confidence: 99%